PENGARUH IKLIM KERJA TERHADAP STRES KERJA GURU DI SMP MUHAMMADIYAH 01 MEDAN - Utami, Nuria Tri; Wijaya, Candra (Jurnal Isema : Islamic Educational Management, 2024)
This research aims to determine the effect of work climate on teacher work stress at SMP Muhammadiyah 01 Medan. This research is survey research which examines the influence of work climate on work stress. The population of this study were teachers at SMP Muhammadiyah 01 Medan with a total of 38 teachers. Data was collected through questionnaires and analyzed using simple statistical regression. The results of hypothesis testing show that work climate has a significant influence on teacher work stress, with an influence size of 12.7% and the rest determined by other circumstances. These findings indicate that work climate is not the only factor that influences teachers' work stress levels, but is an important element that can be improved to reduce stress and improve teacher well-being. Several aspects of work climate that influence work stress include social support, workload, communication, and rewards.